Millennial Voter Behavior in Regional Candidate Elections in Southeast Sulawesi - Sri Afrianti Utami; La Ode Muhammad Adam Nur; Marlina Rajab; Ade Putra (International Journal of Technology and Education Research, 2025)
This study aims to examine, identify, and describe the behavior of millennial voters in regional head elections in Southeast Sulawesi. This study uses a qualitative descriptive approach. Data collection was conducted through in-depth interviews and documentation studies, while data analysis was carried out qualitatively by interpreting the patterns and meanings obtained from the field research results. The results of the study indicate that the behavior of millennial voters is influenced by three main factors, namely sociological, psychological, and rational choice factors. Sociological factors place voting behavior in a social context, where political choices are influenced by demographic and socioeconomic backgrounds, such as family influence, place of residence, education level, occupation, income, religion, and social and cultural similarities. Psychological factors relate to voters' emotional closeness to candidates, such as admiration, personal closeness, and orientation toward candidate figures. Meanwhile, rational choice factors indicate that millennial voters increasingly consider candidates' vision and mission, track record, and previous political experience in making their choice. This study concludes that millennial voters in Southeast Sulawesi tend to exhibit increasingly rational voting behavior, although social and psychological influences still play a role in the political decision-making process